Satisfacción de madres hacia la consejería nutricional y estado nutricional del menor de un año atendidos en la IPRESS, Iquitos 2021 - Vásquez Souza, Daisy Bella (2024)
The objective of the study was to determine the relationship between mothers' satisfaction with nutritional counseling and the nutritional status of children under 1 year of age treated at the Health Services Provider Institution I-3 San Antonio de Iquitos. The research design was non-experimental, the approach was quantitative, since numerical data was collected from the 81 mothers and children between 6 to 11 months who participated in the survey cross sectionally, the results were from 81 participants (100% ), mothers and children who make up the sample, 67 (82.8%), children presented normal nutritional status, and 87.7% (71) mothers were satisfied with the nutritional counseling received. When applying the statistical test of nutritional status of the child under one year of age studied=0.023.